KEPASTIAN HUKUM GREEN BANKING DALAM SISTEM PENYALURAN KREDIT PERBANKAN DI INDONESIA - Yessica Latifa (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2021)
Yessica Latifa, Sihabudin, Syahrul SajidinFaculty of Law Universitas BrawijayaJl. MT. Haryono No. 169 MalangEmail: yessica.latifa98@gmail.comAbstractThis research is aimed at studying green banking policy and slow green bankingdevelopment in Indonesia. Moreover, there are no strict sanctions in the regulation of greenbanking, and the role of the government in paying attention to those involved in greenbanking is minimum. This is a normative law research based on normative case study.There has not been clear legal certainty in the implementation of green banking policy inbanking loan system in Indonesia. The research results conclude that the green bankingpolicy has legal loopholes in it since the regulation is only restricted to administrativesanction, and the role of the government in providing incentive for those in green bankingis considered too little. This provision is not governed in a specific regulation and onlyrefers to the Law concerning Environment.Keywords: state’s policy, green banking, environment, banking, legal loophole